La Estoria de España de Alfonso X: los reinados de Sancho III, Fernando II y Alfonso VIII - Mariano de la Campa Gutiérrez (E-Spania, 2016)
At the moment of the death of king Alfonso X, the Estoria de España, started under his patronage, had not yet been completed. The study of the working techniques of the various teams involved in its preparation has allowed scholars to shade light over the creation process of the Estoria, carried out under the direction of the king. The focus of these studies has been traditionally the part of the history prior to the kings of Castille; only in recent years this interest has turned to the final section of the Crónica. This paper focuses on one of the least studied parts of that section of the Estoria de España, the one covering the kingdoms of Sancho III, Fernando II and Alfonso VIII.